Polycyclic aromatic hydrocarbons bioaccessibility in seafood: Culinary practices effects on dietary exposure - dos Santos Fogaça, Fabíola Helena (2020)
This work aimed to determine the effect of culinary practices on the contamination level and bioaccessibility of polycyclic aromatic hydrocarbons (PAHs) in seafood. The selected farmed seafood species (marine shrimp, clams and seaweed) were commercially available in Portugal. The mean concentrations of PAHs varied between 0.23 and 51.8 µg kg-1, with the lowest value being observed in raw shrimp and the highest in dried seaweed. The number of compounds detected in seaweed and clams (naphthalene, acenaphthene, fluorene, phenanthrene, benzo(b)fluoranthene and benzo(j)fluoranthene) were higher than in shrimp (fluorene and pyrene). Among the PAHs measured, fluorene was the predominant one. There was a significant interaction effect between species and culinary treatment (p < 0.05), thus boiled and dried seaweed samples presented the lowest and the highest levels of fluorene (0.13 and 1.8 µg kg-1), respectively. The daily intake of PAHs decreased with bioaccessibility, varying from 22% for benzo(k)fluoranthene (in raw clam) to 84% for phenanthrene (in steamed clam). According to the potency equivalent concentrations, screening values and bioaccessibility of PAHs, the consumption of marine shrimp, clam and seaweed is considered as safe for consumers.